Analisis Modal Kerja dan Profitabilitas Perusahaan BUMN Bidang Jasa Infrastruktur - Maldania Sundari Dewi; Endang Hatma Juniwati; Ine Mayasari (Indonesian Journal of Economics and Management, 2022)
This research aim to find out the effect of cash turnover, receivable turnover, and inventory turnover to the profitability in the state-owned company in infrastructure service sector simultaneosly and partially. The population in this research were the state-owned company in infrastructure service sector in 2017-2021. The quarterly financial report of PT. Waskita Karya (Persero) Tbk., PT. Wijaya Karya (Persero) Tbk., PT. Semen Indonesia (Persero) Tbk., and PT. Jasa Marga (Persero) Tbk. are being used as sample. The research method use descriptive quantitative by performing panel data regression analysis with using a software called Eviews 9. The result showed that simultaneosly, cash turnover, receivable turnover, and inventory turnover have a positive and significant effect on profitability and partially, both of cash turnover and inventory turnover have a negative and significant effect, receivable turnover has a positive and significant effect on profitability in the state-owned company in infrastructure service sector in 2017-2021.